2017
DOI: 10.3389/fmicb.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SGI1/PGI1 Elements and Resistance to Extended-Spectrum Cephalosporins in Proteae of Animal Origin in France

Abstract: Proteae, and especially Proteus mirabilis, are often the cause of urinary tract infections (UTIs) in humans. They were reported as carriers of extended-spectrum β-lactamase (ESBL) genes, and recently of carbapenemases, mostly carried by the Salmonella genomic island 1 (SGI1) and Proteus genomic island 1 (PGI1). Proteae have also lately become an increasing cause of UTIs in companion animals, but antimicrobial susceptibility data in animals are still scarce. Here, we report the characterization of 468 clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Our data agree with the study in Taiwan which revealed the same prevalence of MDR S. Albany, mediated by SGI1-F in humans and swine, and suggested the clonal dissemination of a SGI1-F-carrying strain in Taiwan (Kuo et al, 2014). In contrast, a Salmonella surveillance study in Scotland during 1990Scotland during -2004 showed differences in the prevalence of SGI1 variants in human and animal isolates, and the independent origin of isolates within each population (Mather et al, 2011 (Schultz, Cloeckaert, Doublet, Madec, & Haenni, 2017). The relationship between animal and human Salmonella isolates regarding SGI1 variants, along with their closely associated PFGE patterns, indicates that food-producing animals may be the source of MDR isolates in humans.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data agree with the study in Taiwan which revealed the same prevalence of MDR S. Albany, mediated by SGI1-F in humans and swine, and suggested the clonal dissemination of a SGI1-F-carrying strain in Taiwan (Kuo et al, 2014). In contrast, a Salmonella surveillance study in Scotland during 1990Scotland during -2004 showed differences in the prevalence of SGI1 variants in human and animal isolates, and the independent origin of isolates within each population (Mather et al, 2011 (Schultz, Cloeckaert, Doublet, Madec, & Haenni, 2017). The relationship between animal and human Salmonella isolates regarding SGI1 variants, along with their closely associated PFGE patterns, indicates that food-producing animals may be the source of MDR isolates in humans.…”
Section: Discussionsupporting
confidence: 90%
“…In a similar study, the PFGE analysis of SGI1‐positive serotype Agona isolates demonstrated identical patterns and was clonally related (Doublet, Butaye, et al (), whereas the study of SGI1 containing Proteus spp. isolates exhibited unrelated PFGE patterns except the six SGI1‐V containing isolates (Schultz, Cloeckaert, Doublet, Madec, & Haenni, ). The relationship between animal and human Salmonella isolates regarding SGI1 variants, along with their closely associated PFGE patterns, indicates that food‐producing animals may be the source of MDR isolates in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Within veterinary strains of Morganellaceae, bla CTX−M−15 (P. mirabilis) and bla CTX−M−1 (P. rettgeri) have been recently reported. In this study, the bla CTX−M−15 gene was even detected in duplicate, one chromosomally-and the other plasmid-located (non-typable) (Schultz et al, 2017).…”
Section: Ctx-msmentioning
confidence: 58%
“…Unfortunately, conjugation was unsuccessful. In addition, the detection of bla VEB-6 and bla NDM-1 in PGI1-PmPEL and bla VEB-6 -carrying SGI1-V in P. mirabilis strains isolated in France are a serious public health threat (10). Recently, we reported the detection of SGI1-PmABB in the P. mirabilis strain PmTAN59 in the same hospital (6).…”
mentioning
confidence: 97%